2020
DOI: 10.1007/s13205-020-2066-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity among aquatic and fecal isolates of Escherichia coli using multilocus variable number of tandem repeat analysis

Abstract: In developing countries like India, fecal pollution of surface waters is a major threat to public and environmental health. The aim of the study was to assess serological, phylogenetic and molecular diversity among aquatic Escherichia coli isolates from Yamuna river and their comparison with the animal fecal isolates. A total of 97 E. coli isolates from Yamuna river and domesticated animals were characterized by multilocus variable number tandem repeat analysis (MLVA) using four VNTR loci. The pathogenicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Studies by Yasir et al [74] and Sun et al [75] reported the genetic diversities in multidrug resistant ESBLproducing E. coli although, our study did not screen for ESBL in the E. coli strains nevertheless provides an opportunity for further analysis. EPEC strains were predominantly isolated from river water samples and our study corroborates with another report by Khare et al [76]. Our current study used ERIC-PCR to identify the various sources and this is supported by Ibekwe et al [77] who reported E. coli isolated from swine wastewater samples in the United States.…”
Section: Discussionsupporting
confidence: 91%
“…Studies by Yasir et al [74] and Sun et al [75] reported the genetic diversities in multidrug resistant ESBLproducing E. coli although, our study did not screen for ESBL in the E. coli strains nevertheless provides an opportunity for further analysis. EPEC strains were predominantly isolated from river water samples and our study corroborates with another report by Khare et al [76]. Our current study used ERIC-PCR to identify the various sources and this is supported by Ibekwe et al [77] who reported E. coli isolated from swine wastewater samples in the United States.…”
Section: Discussionsupporting
confidence: 91%